Biochemical and structural characterisation of a protozoan beta-carbonic anhydrase from Trichomonas vaginalis. (1st January 2020) - Urbański, Linda J.; Di Fiore, Anna; Azizi, Latifeh; Hytönen, Vesa P.; Kuuslahti, Marianne; Buonanno, Martina; Monti, Simona M.; Angeli, Andrea; Zolfaghari Emameh, Reza; Supuran, Claudiu T.; De Simone, Giuseppina; Parkkila, Seppo
Abstract: We report the biochemical and structural characterisation of a beta-carbonic anhydrase (β-CA) from Trichomonas vaginalis, a unicellular parasite responsible for one of the world's leading sexually transmitted infections, trichomoniasis. CAs are ubiquitous metalloenzymes belonging to eight evolutionarily divergent groups (α, β, γ, δ, ζ, η, θ, and ι); humans express only α-CAs, whereas many clinically significant pathogens express only β- and/or γ-CAs. For this reason, the latter two groups of CAs are promising biomedical targets for novel antiinfective agents. The β-CA from T. vaginalis (TvaCA1) was recombinantly produced and biochemically characterised. The crystal structure was determined, revealing the canonical dimeric fold of β-CAs and the main features of the enzyme active site. The comparison with the active site of human CA enzymes revealed significant differences that can be exploited for the design of inhibitors selective for the protozoan enzyme with respect to the human ones.